Abject life and disaster: Opportunity and invasive species governance following the 2019–2020 Australian bushfires. (November 2022) - Atchison, Jennifer; Pilkinton, Mary
Abstract: The 2019–2020 Australian bushfire disaster witnessed extraordinary wildlife death. A key component of the response was killing invasive life that might opportunistically colonise freshly burnt landscapes or prey on what survived. This paper considers the notion of disaster as opportunity in order to examine the ontological politics of governing invasive life. Our focus is twofold: the re-articulation of power over invasive life during disaster reproducing its abjection, and the colonial context in which invasive species management and disaster responses occur. We first consider how invasive life is rendered abject in governance through the application of the 'invasion curve' which preconditions opposition to invasive life, and through a moral politics of neglect, maintains it as unworthy of care. Presenting new empirical analysis of media discourse and responses to invasive life during and after the Australian 2019-2020 bushfires, we then consider the moral geographies of opportunity, including the moral status of different species, and Indigenous responses to the disaster. Responses to invasive species during the fires tended to reproduce existing approaches but responses from Indigenous people suggest that the opportunity of this disaster might be otherwise imagined. In this case, questioning the terms of engagement with invasive life provides possibilities for decolonising invasive species governance, ushering in new obligations and responsibilities.